2010
DOI: 10.1097/bsd.0b013e3181a990fc
|View full text |Cite
|
Sign up to set email alerts
|

Can Iliac Crest Reconstruction Reduce Donor Site Morbidity?

Abstract: This study validates our hypothesis that the donor site morbidity after tricortical iliac crest graft harvesting is probably a structural issue and it can be reduced by reconstruction of the defect. It also highlights the fact that the Chitra-HABG block is an excellent material for reconstruction of the iliac crest defect, as it gets incorporated into the surrounding bone without adverse effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The clinical results for hydroxyapatite have mixed results. Acharya et al [63] found that hydroxyapatite is not suitable as a bone graft substitute. They conducted a prospective, matched, controlled study comparing hydroxyapatite bioactive glass ceramic composite on one side of the posterolateral fusion to autologous bone on the contralateral side in 24 patients.…”
Section: Ceramicsmentioning
confidence: 99%
“…The clinical results for hydroxyapatite have mixed results. Acharya et al [63] found that hydroxyapatite is not suitable as a bone graft substitute. They conducted a prospective, matched, controlled study comparing hydroxyapatite bioactive glass ceramic composite on one side of the posterolateral fusion to autologous bone on the contralateral side in 24 patients.…”
Section: Ceramicsmentioning
confidence: 99%
“…A dense and homogeneous biocomposite was obtained after a heat treatment of the parent glass, which comprised ~38 wt% oxy-FAP (Ca 10 (PO 4 ) 6 (O,F) 2 ) and ~34 wt% β-wollastonite (CaO·SiO 2 ) crystals, 50-100 nm in size in a MgO-CaO-SiO 2 glassy matrix. 206,[1015][1016][1017][1018][1019][1020][1021][1022][1023][1024][1025] A-W glassceramics are an assembly of small apatite particles effectively reinforced by wollastonite. The bending strength, fracture toughness and Young's modulus of A-W glass-ceramics are the highest among bioactive glass and glass-ceramics, enabling them to be used in some major compression load-bearing applications, such as vertebral prostheses and iliac crest replacement.…”
Section: Injectable Bone Substitutes (Ibs)mentioning
confidence: 99%
“…Bioactive glasses belonging to Calcium phosphate silicate group have very good bonding properties with bone and soft tissues [9]. This is a biologically active compound and it encourages rapid new bone growth; as the surface integration is chemical in nature, tissue adhesion starts almost immediately and optimum interface strength is attained within weeks [9, 10]. This composite of HAP and bioactive glass ceramics presents beneficial properties of both the individual components [9].…”
Section: Introductionmentioning
confidence: 99%
“…Previous study has shown lesser donor-site morbidity after ceramic block application in the iliac crest bone graft donor site. Both ceramic materials have been used in spine and trauma surgeries and in Orthopaedic procedures [1012].…”
Section: Introductionmentioning
confidence: 99%